Efektivitas Model Project Based Learning dalam Kurikulum Merdeka terhadap Literasi Sains Siswa MTs - Arif Sholehudin (IEC: Journal of Educational Innovation, 2026)
This study aims to examine the effectiveness of the Project Based Learning (PjBL) model within the Merdeka Curriculum in improving students’ scientific literacy at the Islamic junior high school (MTs) level. The research employed a quasi-experimental design with a non-equivalent control group. The sample consisted of two classes: an experimental class taught using PjBL and a control class taught using conventional methods. Data were collected through pretest and posttest instruments measuring scientific literacy, including content knowledge, scientific competencies, and application in real-life contexts. The results indicated a significant improvement in the experimental class, as reflected by higher posttest scores and a moderate to high N-Gain compared to the control class. Students engaged in project activities demonstrated better critical thinking, problem-solving skills, and conceptual understanding. The findings suggest that PjBL is an effective and relevant instructional model to support the implementation of the Merdeka Curriculum and to enhance scientific literacy comprehensively among MTs students.